Proposed Handwriting Arabic Words classification Based On Discrete Wavelet Transform and Support Vector Machine - Hassan, Alia Karim Abdul; Alawi, Mohammed (Iraqi Journal of Science, 2022)
A proposed feature extraction algorithm for handwriting Arabic words. The proposed method uses a 4 levels discrete wavelet transform (DWT) on binary image. sliding window on wavelet space and computes the stander derivation for each window. The extracted features were classified with multiple Support Vector Machine (SVM) classifiers. The proposed method simulated with a proposed data set from different writers. The experimental results of the simulation show 94.44% recognition rate.